BAKU TOLONG, TORANG SAMUA BASUDARA: MODAL SOSIAL DAN TITIK TEMU DALAM MENGELOLA KERAGAMAN ETNORELIGIUS DI WILAYAH TRANSMIGRASI DUMOGA, SULAWESI UTARA (Harmoni, 2022)
This paper present with a new perspective in understanding the management of ethnic and religious (ethnoreligious) diversity in Indonesia. The purpose of this study is to explore the management of ethnic and religious diversity between the Mongondownese-Muslim, Minahasanese-Christian community and the Balinese-Hindu community in the transmigration area, Dumoga, Bolaang Mongondow Regency, North Sulawesi Province. This research is important because it can enrich previous studies on the dynamics of relations between communities of different ethnicities and religions, especially in reframing efforts to create harmony in the life of the nation, religion, and society. Qualitative methods with a sociological-anthropological approach, as well as in-depth observations and interviews were used as the main instrument to obtain data. The findings of this study indicate that social capital is an important keyword in building religious harmony in the Dumoga area. The social capital in question is Baku Tolong and the jargon of Torang Samua Basudara. This social capital has become a meeting point between different ethnoreligious communities in the Dumoga area for a long time which has been functional in an effort to care for and maintain religious harmony.
Keywords: Mengelola Keragaman, Modal Sosial, Titik Temu, Dumoga